THE STATUS OF THE STATE IN INTERNATIONAL AGREEMENTS IN THE ERA OF GLOBALIZATION: A PRIVATE INTERNATIONAL LAW PERSPECTIVE - Yulian Dwi Nurwanti (Journal of International Islamic Law, Human Right and Public Policy, 2026)
Globalization has driven an increase in cross-border civil law relationships involving various legal subjects from different jurisdictions. This situation gives rise to various legal issues, such as conflicts of laws, the determination of applicable law, court jurisdiction, and the recognition and enforcement of foreign judgments. In this context, international treaties serve as vital legal instruments for harmonizing norms and providing legal certainty for international civil law relationships. As subjects of international law, states hold a strategic position in the formation, ratification, and implementation of international treaties within national legal systems. This study aims to analyze the position of the state regarding international treaties in the era of globalization from the perspective of Private International Law and to examine how states implement these treaties to regulate cross-border civil law relationships. The study employs a normative legal research method, using both the statute approach and the conceptual approach. Legal materials—comprising primary, secondary, and tertiary sources—were analyzed qualitatively using a descriptive-analytical method. The findings indicate that the state holds a fundamental position as a subject of international law, possessing the authority to form, ratify, and implement international treaties as an exercise of state sovereignty. From the perspective of Private International Law, the implementation of international treaties serves to harmonize national law with international norms, provide legal certainty for cross-border civil law relationships, and minimize potential conflicts of laws.